Analisis Tingkat Literasi Keuangan Syariah Petani Padi Di Desa Sei Penggantungan Kabupaten Labuhanbatu - Ahmad Suwandi; Marliyah Marliyah (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Sei Penggantung Village, Labuhanbatu Regency, is an underdeveloped village starting to develop. Having the majority of the population working as rice farmers makes farmers during the farming period always need capital, but often in farming activities, farmers are always constrained by money. Farmers always borrow from conventional financial services in the village when there is a shortage of capital. This does not solve the problem but creates a new trial, namely interest-bearing debt, so a new financing system is needed that avoids interest. Islamic financial institutions can be an option for farmers as a source of capital. The aim is to assess knowledge of Islamic finance among farmers. The study was conducted from October 2022 to January 2023. It used four indicators to measure Islamic financial literacy: Islamic savings and loans, basic knowledge of Islamic finance, Islamic investment, and Islamic insurance. A survey method was used to collect data, and a sample of 30 individuals was selected through purposive sampling. Data collection was carried out by interviewing using a questionnaire, and previously the questionnaire items were validated and tested for reliability. Descriptive statistics were used for analysis. The results showed that the level of Islamic financial literacy among rice farmers in Sei Penggantungan Village was low, with an index value of 59.66%. According to the classification of Chen and Volpe (1998), it is included in the low category (<60%). The main factor causing low Islamic financial literacy among farmers is the limited access of rural communities to financial education related to Islamic financial services. This includes understanding the features, benefits, risks, rights, and obligations associated with the service. This drives the lack of public interest in using Islamic financial services causing farmers to continue to rely on moneylenders to find sources of capital.